Neoproterozoic granitoid magmatism and granulite metamorphism in the Chu-Kendyktas terrane (Southern Kazakhstan, Central Asian Orogenic Belt): Zircon dating, Nd isotopy and tectono-magmatic evolution - Tretyakov A.A.; Pilitsyna A.V.; Degtyarev K.E.; Salnikova E.B.; Kovach V.P.; Lee H.-Y.; Batanova V.G.; Wang K.-L.; Kanygina N.A.; Kovalchuk E.V. (My University, 2019)
Within the Chu-Kendyktas Precambrian terrane located in Southern Kazakhstan (in the western part of the Central Asian Orogenic Belt), medium- and high-grade metamorphic formations have been identified and attributed to the Aydaly and Shukyr Complexes. The Aydaly Complex is predominantly composed of orthogneisses with a Neoproterozoic protolith age of 790 Ma and subordinate high-temperature granulites comprising a succession of amphibolites, amphibole-rich granulites, mesocratic granulites, and melanocratic (clinopyroxene-rich) and leucocratic (melt-rich) granulites, which were evidently formed at moderate pressures of 6–9 kbar and high temperatures, increasing from 700 to 900 °C or more. The clinopyroxene-rich granulites of the Aydaly Complex contain detrital zircon grains of mainly Palaeoproterozoic (1790–2058 Ma) and, to a more limited extent, Neoarchean (~2500 Ma) ages, with preserved magmatic zoning and indicating a sedimentary origin of the protolith via mafic greywackes that were subsequently metamorphosed to amphibolites. The age estimates of the leucocratic melt-rich granulites, which form veins or layers within the clinopyroxene-rich melanosome, correspond to the range 770–790 Ma and define the Neoproterozoic stage of magmatism and granulite metamorphism. Hence, the deposition of the sedimentary protolith for the Aydaly Complex granulites and its subsequent emplacement at mid-crustal levels occurred from the middle Palaeoproterozoic (~1800 Ma) to the late Tonian (~770–790 Ma). In turn, the Shukyr Complex consists of garnet-biotite schists, which are characterised by a significantly lower grade of metamorphism compared to the Aydaly Complex, at around T ~600 °C. The garnet-biotite schists are thought to represent moderate-temperature hornfels, located at the contact between the protolith (shales) and the Early Palaeozoic Ulken massif granitoids. The deposition of the Shukyr Complex protolith occurred during the Ediacaran–Cambrian, as a result of the erosion of mainly Mesoproterozoic (1000 Ma), and to a lesser extent Palaeoproterozoic (2460 Ma), rocks. The Sm-Nd whole-rock isotopic compositions suggest that the formation of the protoliths of the Aydaly and Shukyr Complexes was related to the reworking of Palaeoproterozoic continental crust.
Keywords: Central Asian Orogenic Belt; Neoproterozoic; Zircon dating; Sm-Nd isotope systematics; High-temperature granulite; Granitoid magmatism; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Neoproterozoic